Analysis of the effect of musical stimulation on cortical auditory evoked potentials - De Lima, Daiane Damaris Baptista [UNESP]; Regaçone, Simone Fiuza; De Oliveira, Anna Caroline Silva [UNESP]; Alcântara, Yara Bagali [UNESP]; Chagas, Eduardo Federighi Baisi [UNESP]; Frizzo, Ana Claudia Figueiredo [UNESP] (Thieme, 2019)
Introduction Cortical auditory evoked potentials (CAEPs) are bioelectric responses that occur from acoustic stimulations, and they assess the functionality of the central auditory system. Objective The objective of the present study was to analyze the effect of musical stimulation on CAEPs. Methods The sample consisted of 42 healthy female subjects, aged between 18 and 24 years, divided into two groups – G1: without musical stimulation prior to the CAEP examination; and G2: with stimulation prior to the examination. In both groups, as a pre-collection procedure, the complete basic audiological evaluation was performed. For the musical stimulation performed in G2, we used an MP4 player programmed to play Pachelbel’s “Canon in D Major” for five minutes prior to the CAEP examination. To analyze the effect on the groups, the ear side and the ide–group interaction, a mixed analysis of variance (ANOVA) of repeated measures was performed. Box M test and Mauchly sphericity test were also performed. Results Test differences were considered statistically significant when the p-value was < 0.05 (5%). Thus, it was possible to observe that there was a statistically significant difference of the P2 component characterized by the decrease in the amplitude of response in the left ear in G2 when comparing the responses of CAEP with and without prior musical stimulation. Conclusion The result of the present study enabled us to conclude that there was a change in the response of CAEPs with musical stimulation.
Keywords: Auditory evoked potentials; Electrophysiology; Music